Relações socioambientais na recuperação florestal da sub-bacia hidrográfica do Rio Poxim, Sergipe - Gonçalves, Bruno Villaça (2013)
In Sergipe State the remaining Atlantic Forest area is estimated at about 9% of its original area. One of the vegetation areas most impacted is the springs and riparian forests of river. In this sense, some actions have been developed as a way to reverse this situation of degradation, such as public policy and forest recovery projects. One of such actions is the Preserving Springs and Municipalities Program, from which was developed the forest recovery project for the Sub-basin of Poxim river. In this context, it is paramount importance to understand how these actions have been carried out, how social participation happens and what the perception of the different social actors involved is, trying to reflect on the effectiveness that such actions have in the medium and long term. The research had as general objective to analyze the social participation in the forest recovery process in the Sub-basin of Poxim River. For this purpose, it was traced the following specific objectives: (1) understand how the historical process of forest recovery occurred in Sergipe State and the current context; (2) understand the concepts and identify the roles of institutions regarding forest recovery in Sergipe; (3) analyze how such actions are carried out and how the involvement and environmental perception of rural producers happens; (4) understand which aspects contribute or hamper the participation of rural producers in the forest recovery actions. Semi-structured interviews were conducted with 12 representatives of institutions and 11 rural producers involved in recovery actions. Such interviews were analyzed based on secondary sources, such as official documents and bibliography in the case of institutions; and based on the methodology of Collective Subject Discourse (DSC), in the case of rural producers. The results indicate three levels of participation: functional, by incentives and passivity, indicating the need to reformulate the proposal of involvement and social participation in the projects. An important topic among the demands is the need to reconcile productive points with the forest recovery. With respect to the institutional aspect, the demand for strengthening institutional arrangement, this contributes to financing, medium-and long-term planning, and creating tools that empower the forest recovery in Sergipe State.